“Identificación del perfil de polifenoles, flavonoides y metilxantinas en mazorca y placenta de cacao (theobroma cacao, l.) De las variedades ccn-51 y nacional” - Chuez Sabando, Katherine Pamela (2022)
In the present investigation, the phenolic and alkaline profile of residual samples of cocoa pods and placenta of the NacionalxTrinitario variety and CCN-51 clone were identified, which were extracted from the "La Cruz" Farmers' Association of the Mocache canton belonging to the Province of Los Rios, Ecuador. Within the polyphenol profile, the phenolic compounds were determined using the HPLC technique; using standards of Catechin, Epicatechin, Procyanidin B1, B2 and C1. In the same profile, polyphenols of unidentified origin were found in the residual samples, whose concentrations are named as follows. In the placenta, 4-hydroxy benzoic acid (45,9678 ± 25,41 to 10,028 ± 25,41 µg· g −1 ), Vanillic